Perancangan Sistem Manajemen Mutu ISO 9001:2015 di PT. Gunung Marmer Raya - Timothy Sebastian; Jani Rahardjo (Jurnal Titra, 2021)
The purpose of this research is to design a quality management system based on ISO 9001:2015 at PT. Gunung Marmer Raya. The research begins with gap analysis by doing an interview with top management of the company. Based on the gap analysis, only 23.39% of company’s activities correspond with the international standard. Due to this analysis, a new quality management system based on ISO 9001:2015 was required by the company who competes in international level. The research continues by creating the Strength and Weakness analysis, risk analysis, quality objectives, job description, and competition table, Standard Operating Procedure, and Work Instruction. Also include in this research, the internal audit to evaluate the implementation of the new quality management system. Consenquence analysis was done as the last step of this research. This analysis includes gap analysis after the design of clauses and impact analysis for the company. The final number of the fulfillment of ISO 9001:2015 is 82.91%.